Susceptibility of functional impairment scales to noncredible responses in the clinical evaluation of adult ADHD - Fuermaier, Anselm B. M.; Weisbrod, Matthias (The clinical neuropsychologist, 2018)
Objective: A growing body of research questions the reliance of symptom self-reports in the clinical evaluation of attention-deficit/hyperactivity disorder (ADHD) in adulthood. A recent study suggested that also impairment reports are vulnerable to noncredible responses, as derived from a simulation design using a global functional impairment scale. The present study aims to add evidence to this issue, by using an ADHD specific impairment scale in a simulation design on large samples. Method: Impairment ratings on the Weiss Functional Impairment Rating Scale (WFIRS) of 62 patients with ADHD were compared to 142 healthy individuals who were instructed to show normal behavior. Furthermore, impairment ratings of patients with ADHD were compared to ratings of 330 healthy individuals who were randomly assigned to one of four simulation conditions that were instructed to complete the scale as if they had ADHD. Results: Patients with ADHD reported higher levels of impairment than the healthy control group in all domains of life. Furthermore, individuals instructed to feign ADHD indicated higher levels of impairments in most domains of life compared to control participants and genuine patients with ADHD. The group differences between individuals feigning ADHD and individuals with genuine ADHD, however, were only small to moderate. Further analyses revealed that the WFRIS was not useful to successfully differentiate genuine from feigned ADHD. Conclusions: The present study confirms the conclusion that self-reported impairments are susceptible to noncredible responses and should be used with caution in the clinical evaluation of adult ADHD.